2022
DOI: 10.7860/jcdr/2022/55780.16821
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice towards COVID-19 Vaccination among Medical Students in a Tertiary Care Hospital of Southern India

Abstract: Introduction: Coronavirus Disease-2019 (COVID-19) vaccination plays an important role in controlling the current pandemic. This may have an impact on other healthcare workers in understanding the importance of COVID-19 vaccination. Aim: To assess the Knowledge, Attitude and Practice (KAP) towards COVID-19 vaccination among medical students in a Tertiary care hospital, Southern India. Materials and Methods: This was an observational crosssectional questionnaire based study done in Mahatma Gandhi Medical Colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…6 In this study females (61.66%) were involved a higher percentage which was similar to the study done by Bhartiya et al 9 In the current study maximum involvement among students, second years MBBS 89 (29.6%) which is not similar to the study done by Vanathy et al showed third-year students 247 (61.8%). 10 The second-year students show high-grade knowledge 32 (36%) and they also had 42.7% of positive attitude and only 31.5% good practice. This student needs more awareness regarding COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 94%
“…6 In this study females (61.66%) were involved a higher percentage which was similar to the study done by Bhartiya et al 9 In the current study maximum involvement among students, second years MBBS 89 (29.6%) which is not similar to the study done by Vanathy et al showed third-year students 247 (61.8%). 10 The second-year students show high-grade knowledge 32 (36%) and they also had 42.7% of positive attitude and only 31.5% good practice. This student needs more awareness regarding COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 94%
“…Globally, hesitancy towards COVID-19 vaccines was associated with education levels, awareness, misinformation, governmental efforts, and fear about infertility [27]. The occurrence of side effects after vaccination is the other concern that results in poor vaccine uptake [28,29]. Some of the common post-vaccination effects were pain at the injection site, lethargy, and fever [30,31].…”
Section: Discussionmentioning
confidence: 99%